The Design and Experimentation of a Wheeled-Chassis Potato Combine Harvester with Integrated Bagging and Ton Bag-Lifting Systems - Hucun Wang; Wuyun Zhao; Wei Sun; Xiaolong Liu; Ruijie Shi; Hua Zhang; Pengfei Chen; Kuizeng Gao (Agriculture)
The mechanized harvesting level of potatoes in the arid areas of Northwest China is low and mainly relies on simple machinery to dig the soil surface, and then people manually pick up and bag the potatoes. This harvesting method has the problems of a high labor intensity, low operation efficiency, and high labor cost. Based on this, a wheeled-chassis potato combine harvester with integrated bagging and ton bag-lifting systems was developed, which could complete potato digging, potato–soil separation, potato–film separation, automatic bagging, and field ton bag lifting in one go. Firstly, based on the agronomic requirements and unique terrain characteristics of potato planting in this area, the structural design of the whole machine was completed with SOLIDORKS 2019 3D software. Secondly, the dynamic model was established for a numerical analysis, and the core parameters of key components were determined. The field experiments showed that the potato loss rate was 2.1%, the potato damage rate was 1.7%, the skin breaking rate was 2.5%, the impurity content was 1.9%, and the productivity was 0.15~0.23 hm2/h. The above field test indexes met the requirements of national and industrial standards.